Adivasis Betrayed: Adivasi Land Rights in Kerala - C R Bijoy (Economic and Political Weekly May 29, 1999, 1999)
Over the past century and more, tribal lands have been bought by non-tribals at throwaway prices. There has been legislation to check this trend and also to restore alienated lands to tribals. But the will to implement these laws on the part of the government has been missing. Kerala has recently passed a bill, purportedly to protect the interests of the tribals, which makes restoration of land to tribals almost impossible.